RESPON TANAMAN JARAK PAGAR (Jatropha curcas L) TERHADAP LIMA DOSIS ZAT PENGATUR TUMBUH (ZPT) ASAM NAFTALEN ASETAT (NAA) - Elda Nurnasari; - Djumali (Agrovigor, 2012)
Productivity improvement of physic nut can be done by the increase of female flowers numbers. Introducing of plant growth regulators (PGR )is one of many ways to stimulate flowering. The research was aimed to determine the dose of plant growth regulators NAA (Naphthalene Acetic Acid) which can increase the level of production and oil contents. This research was conducted at the Asembagus Experimental for 12 months. Five doses of 500, 1000, 1500, 2000, and 2500 ppm NAA were applied on two years old of J. curcas and arranged in a randomized block design with three replications. For comparison, treatment without PGR was added in treatments. The results showed that NAA application affected the growth plant height, canopy diameter and number of branches and production of fruit numbers, 100-seed weight and oil contents of jatropha. PGR application was able to increase the number of fruit and weight of 100-seed each for 26.64 and 2.07%, respectively, and to reduce the oil contents of 3.05% untreated PGR. Dose of 1000 ppm NAA was able to increase the fruit number and weight of 100-seed each for 35.09 and 2.99%, respectively and reduce the oil contents of 3.58%.